2016
DOI: 10.18632/oncotarget.6972
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-203 suppresses invasion and epithelial-mesenchymal transition induction via targeting NUAK1 in head and neck cancer

Abstract: Head and neck squamous cell carcinoma (HNSCC) has a high capacity for invasion. To identify microRNAs (miRNAs) that regulate HNSCC invasion, we compared miRNA expression profiles between a parent HNSCC cell line and a highly invasive clone. The miR-200 family and miR-203 were downregulated in the clone. Here we focused on the role of miR-203 in invasion and epithelial-mesenchymal transition (EMT) induction in HNSCC. miR-203 was downregulated during EMT induction. Moreover, ectopic overexpression of miR-203 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 50 publications
(58 reference statements)
4
47
0
Order By: Relevance
“…miR‐203 is another microRNA frequently deregulated in different types of cancer (Li, Gao, & Zhang, ; Tang et al., ; Tian et al., ; Zhao et al., ). Focusing on this specific miRNA, our findings are corroborating previous studies reporting a tumor suppressor role of miR‐203 in HNSCC, as miR‐203 expression was significantly downregulated in patients with lymph node metastasis (Benaich et al., ; Obayashi et al., ). These studies showed that miR‐203 inhibited HNSCC invasion and epithelial–mesenchymal transition by targeting a network of prometastatic proteins, including LASP1, SPARC, and NUAK1 (Benaich et al., ; Obayashi et al., ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…miR‐203 is another microRNA frequently deregulated in different types of cancer (Li, Gao, & Zhang, ; Tang et al., ; Tian et al., ; Zhao et al., ). Focusing on this specific miRNA, our findings are corroborating previous studies reporting a tumor suppressor role of miR‐203 in HNSCC, as miR‐203 expression was significantly downregulated in patients with lymph node metastasis (Benaich et al., ; Obayashi et al., ). These studies showed that miR‐203 inhibited HNSCC invasion and epithelial–mesenchymal transition by targeting a network of prometastatic proteins, including LASP1, SPARC, and NUAK1 (Benaich et al., ; Obayashi et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Focusing on this specific miRNA, our findings are corroborating previous studies reporting a tumor suppressor role of miR‐203 in HNSCC, as miR‐203 expression was significantly downregulated in patients with lymph node metastasis (Benaich et al., ; Obayashi et al., ). These studies showed that miR‐203 inhibited HNSCC invasion and epithelial–mesenchymal transition by targeting a network of prometastatic proteins, including LASP1, SPARC, and NUAK1 (Benaich et al., ; Obayashi et al., ). Altogether, our results reinforce the hypothesis that miR‐203 may be a potential new diagnostic and therapeutic target for the treatment of HNSCC.…”
Section: Discussionsupporting
confidence: 90%
“…Up to recent years, it has become increasingly apparent that miRNAs are critical regulators of a wide variety of biological processes, including EMT and tumorigenesis. It has been reported that miR-10b and miR-203 can promote or suppress cancer metastasis and invasion by modulating EMT [27,28]. The present study revealed that mesenchymal markers, such as N-cadherin and vimentin, were down-regulated, but epithelial cell markers, such as E-cadherin were up-regulated in PCa cells overexpressing miR-802 , indicating that miR-802 suppresses EMT.…”
Section: Discussionsupporting
confidence: 51%
“…As already reported, ARK5, as a downstream substrate of Akt, was directly activated by phosphorylation at its Ser 600 , and therefore resulting in stimulation of cancer cells invasion and metastasis [15]. To date, ARK5 has been confirmed to facilitate cancer metastasis through the induction of EMT or the activation of matrix metalloproteinase 2 (MMP2) and MMP9 in certain human malignancies [20, 26-28]. However, few investigations about the effect of ARK5 on the GC invasion and metastasis have been reported.…”
Section: Discussionmentioning
confidence: 93%